Time, culture, and mass play. Issue 4 (2nd October 2022) - Lebed, Felix
ABSTRACT: Playing masses interact and communicate in an uncertain and topsy-turvy behavioral environment freed, curbed, and evaluated by cultural norms. Through collective effort, this issue has been studied in depth (e.g., Huizinga, 1938, [1949]; Bakhtin, 1984; Sutton-Smith, 2008). The play of the masses is usually considered an escape toward a pleasurable 'there', in which a person in a crowd becomes not him/herself for a while. However, when play is ritualized, linked to the sacral and fixed in the cultural tradition of socio-cultural interactions of the masses, it exhibits properties that have not yet been analyzed in depth. Specifically, I suggest that, despite the tendency to see play as a search for pleasurable escape from routine, the further back one regresses in history, the less mass play is connected with joy and entertainment and the more it is linked to elements of the unsettling and suspenseful sacral experience of identity and deep dramatic catharsis. This 'serious' aspect of mass play can also be seen in contemporary sports fandom which, in specific contexts, can be interpreted as a special and even 'sacral' kind of play.